Access and quality of health care in Canada: Insights from 1998 to the present. Issue 6 (November 2020) - Samuelson-Kiraly, Claire; Montague, Terrence; Nemis-White, Joanna; MacPherson, Nicole; Martin, Lesli; Aylen, John; Gogovor, Amédé; Mitchell, Jonathan I.
This article reviews perceptions of Canada's public and health professionals regarding access and quality of healthcare. Principal data sources were 13 sequential Health Care in Canada (HCIC) surveys, from 1998 to 2018. Over time, the data series reveals that an increasing majority of the public report receiving quality care, rising from a national average of 53% in 2002 to 61% in 2018. Regionally, the variation in quality care has been relatively narrow, ranging from 52% in the Atlantic and Prairie provinces to 65% in Ontario in 2018. Professionals' ratings for delivery of quality care in 2018 were slightly higher than the public, averaging 65% and ranging from 58% among nurses to 72% and 74% among physicians and administrators. Despite the favourable ratings received for quality of healthcare, a persistent and growing issue in all regions of the country is concern around timely access to care. In 1998, 4% of the public rated prolonged wait times as a concern; in 2018, 43% rated it as their greatest concern. Regionally, the variation in 2018 ranged from 34% in the Atlantic provinces to 49% in Alberta. This concern about timely access involves all major components of healthcare delivery and is anticipated to worsen. Proposals to improve timely access have been suggested, with interdisciplinary, team-based care being the most strongly supported proposal. The Canadian Medicare system is currently recognized as a valued component of our national identity. However, sub-optimal access continues to undermine quality of care. In the absence of improved access, healthcare quality and outcomes will also remain sub-optimal.